رضاء أعضاء هيئة التدريس على التطبيقات العملية ومشاريع التخرج في مؤسسات التعليم التقني: دراسة ميدانية على عينة من مؤسسات التعليم التقني بمدينة بنغازي. (Economic studies journal, 2022)
This study aims to identify the satisfaction of the Faculty members in technical education institutions about practical applications, graduation projects. To achieve the purpose of the study, a questionnaire was designed and distributed to a sample of (6) ) Technical education institutions in the city of Benghazi, The questionnaire consisted of two parts, the first included demographic data about the respondents in the study; and the second included data related to practical applications and graduation projects. The descriptive analytical approach was also used to analyze the study data and test its hypotheses to reach the results of the study. Finally, the findings of the study clearly show that; There is satisfaction from faculty members on practical applications and graduation projects.